The Pursued Public Service Exam: The general (in)applicability of Article 10 of the Federal Supplementary Law nº 173/2020 (Research, Society and Development, 2022)
The Coronavirus (Covid-19) pandemic has had immediate consequences for public health and the economy at an international level, also bringing with it a concern about the directions that the Public Administration should follow, especially due to the economic crisis that has begun. Among the affected areas were public service exams, especially those with validity ending in the pandemic exception period. In this context, with the advent of the Federal Supplementary Law nº 173/2020, the possibility of suspending the validity period of the competitions nationally began to be discussed, and the following question arises: the aforementioned legal statute would apply to public service exams of all entities and levels or just the Union? The present work focused on this discussion and, according to a study based on the qualitative method, based on research in doctrine, jurisprudence, legislation and technical notes, it walked towards the political-administrative autonomy of each federative entity in deciding on the subject, so that the said law does not have general applicability to all public service exams carried out in the country, except those within the competence of the Union.